Decision Support System in Determining the Best Employees of the Bengkulu Provincial Social Service Using the SAW Method - Angely Rahmadanti; Sapri Sapri; Indra Kanedi (Jurnal Media Infotama, 2025)
In an effort to improve the performance and professionalism of employees, the Social Service of Bengkulu Province annually conducts an evaluation or assessment to determine the best employees as a form of appreciation for the performance of these employees. However, in its implementation, this process experiences obstacles in terms of objectivity and efficiency in conducting assessments, because it still uses a manual process. Therefore, to overcome these problems, this research develops a Decision Support System (SPK) using Simple Additive Weighting (SAW) method to increase objectivity and efficiency in assessing the best employees. This system is developed using PHP programming language and using MySQL database. Based on the results of data testing as many as 5 alternative employees, the results obtained one employee with the highest score on behalf of Zulkifli with a value of 0.931 and declared the best employee